'The Mona Chronicle': the archaeology of early religious encounter in the New World. (19th July 2016) - Cooper, Jago; Samson, Alice V.M.; Nieves, Miguel A.; Lace, Michael J.; Caamaño-Dones, Josué; Cartwright, Caroline; Kambesis, Patricia N.; Frese, Laura del Olmo
Abstract: Abstract : The Caribbean island of Mona, on a key Atlantic route from Europe to the Americas, was at the heart of sixteenth-century Spanish colonial projects. Communities on the island were exposed to the earliest waves of European impact during a critical period of transformation and the forging of new identities. One of many caves within an extensive subterranean world on the island was marked both by indigenous people and by the first generations of Europeans to arrive in the New World. This account of spiritual encounters provides a rare, personalised insight into intercultural religious dynamics in the early Americas.